Reconstitution of the base excision repair pathway for 7,8-dihydro-8-oxoguanine with purified human proteins - Pascucci, B. (Oxford University Press, 2002)
In mammalian cells, repair of the most abundant endogenous premutagenic lesion in DNA, 7,8-dihydro-8-oxoguanine (8-oxoG), is initiated by the bifunctional DNA glycosylase OGG1. By using purified human proteins, we have reconstituted repair of 8-oxoG lesions in DNA in vitro on a plasmid DNA substrate containing a single 8-oxoG residue. It is shown that efficient and complete repair requires only hOGG1, the AP endonuclease HAP1, DNA polymerase (Pol) β and DNA ligase I. After glycosylase base removal, repair occurred through the AP lyase step of hOGG1 followed by removal of the 3′-terminal sugar phosphate by the 3′-diesterase activity of HAP1. Addition of PCNA had a slight stimulatory effect on repair. Fen1 or high concentrations of Pol β were required to induce strand displacement DNA synthesis at incised 8-oxoG in the absence of DNA ligase. Fen1 induced Pol β strand displacement DNA synthesis at HAP1-cleaved AP sites differently from that at gaps introduced by hOGG1/HAP1 at 8-oxoG sites. In the presence of DNA ligase I, the repair reaction at 8-oxoG was confined to 1 nt replacement, even in the presence of high levels of Pol β and Fen1. Thus, the assembly of all the core proteins for 8-oxoG repair catalyses one major pathway that involves single nucleotide repair patches.